Comparison of amino acid profile in the juice of six pomegranate cultivars from two cultivation regions in China. Issue 5 (9th January 2017) - Li, Yingcan; Gu, Pan; Wang, Liwei; Wang, Shaoyang; Yang, Hangyu; Zhang, Bolin; Zhu, Baoqing; Ma, Chao
Abstract: The physicochemical index and the composition of amino acids of six pomegranate cultivars from two regions in China were analyzed and compared in this study. Results showed that the levels of titratable acid and reducing sugar were found higher in the Xinjiang pomegranate juices, while those from Shandong contained more total amino acids. Regarding individual amino acids, the total glutamate‐related, aspartate‐related, pyruvate‐related, and serine‐related amino acids were higher in the Shandong pomegranate juices, while the total aromatic amino acids contents were higher in Xinjiang pomegranate juices, although they were not as comparable as the other amino acids. Cluster analysis revealed that pomegranate cultivars could be clearly separated according to their growing regions based on amino acid profile, suggesting that regional characteristics had a significant influence on the accumulation of amino acids in pomegranate. Genotype appeared to be another significant factor that resulted in the segregation in the same region. Practical applications: Amino acids are the important nutrients in the juice of pomegranate. They play important roles in affecting the sensory attributes of the pomegranate juice. The present study revealed that the composition and content of amino acids in the pomegranate juices from the Shandong and the Xinjiang regions of China was significantly affected by their regional characteristics and genotypes. The findings from this study could provide reference on the development of pomegranate cultivation.